Cortical macro- and microstructural changes in isolated rapid eye movement sleep behavior disorder - Jèssica Pardo; Ignacio Roura; Victor Montal; Cristina Martín-Barceló; Javier Oltra; Anna Campabadal; Núria Bargalló; Mònica Serradell; Gerard Mayà; Angelica Montini; Carles Gaig; Claustre Pont-Sunyer; et al. (npj Parkinson's Disease)
Abstract Cortical mean diffusivity (cMD), a marker of cortical microstructural changes in neurodegenerative disorders, remains unexplored in isolated REM sleep behavior disorder (iRBD), a prodromal stage of Lewy body (LB) diseases. Its relationship with cortical thickness (CTh), clinical features, and neuropsychological performance is also unknown. We assessed cMD and CTh in thirty-six patients with iRBD at high risk of conversion and 29 healthy controls (HC), examining associations with clinical and cognitive measures. Effect sizes were calculated using Cohen’s d. Patients with iRBD showed increased cMD in rostral and caudal cortical regions compared to HC (d > 0.5). Cortical thinning was restricted to caudal areas. Higher cMD correlated with longer iRBD duration, later onset, MDS-UPDRS III, apathy, and poorer performance on Grooved Pegboard and Symbol-Digit Modality Tests. These findings suggest that cMD may be more sensitive than CTh and serve as a valuable imaging biomarker for detecting early cortical changes in prodromal LB diseases.